POLYMORPHISM OF THE MDR1 GENE IN PATIENTS WITH CHRONIC GASTRITIS - Ochilov Alisher Kamilovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The article discusses the results of genotyping patients to improve the pharmacotherapy of acid-dependent diseases of the digestive system by the CYP2C19 gene, which provides the pharmacokinetics of drugs from the proton pump inhibitor group contributed to improving the effectiveness, safety and personalization of pharmacotherapy, which serves to improve the quality of life of patients.